2010
DOI: 10.1002/cncr.25012
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative evaluation of a quantitative immunochemical fecal occult blood test to determine its optimal clinical use

Abstract: BACKGROUND: Quantified, human hemoglobin (Hb)-specific, immunochemical fecal occult blood test (IFOBT) measurements are now used for colorectal cancer (CRC) screening. The objective was to evaluate sensitivity and specificity for CRC and advanced adenomatous polyps (APs) by the fecal Hb threshold used to determine a positive test and the number of IFOBTs prepared per test, so as to determine the least number of colonoscopies required to detect a neoplasm. METHODS: Cumulative data were analyzed from a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 30 publications
2
37
0
2
Order By: Relevance
“…Rozen et al found that for screening average-risk subjects 95% specificity for CRC was achieved by using a one-sample quantitative FIT with a 20 ug Hb/g threshold (21). Our study shows that the optimal threshold changes when considering age and sex.…”
Section: Thresholds Without Considering Clinical Capacity Of Colonoscopymentioning
confidence: 56%
“…Rozen et al found that for screening average-risk subjects 95% specificity for CRC was achieved by using a one-sample quantitative FIT with a 20 ug Hb/g threshold (21). Our study shows that the optimal threshold changes when considering age and sex.…”
Section: Thresholds Without Considering Clinical Capacity Of Colonoscopymentioning
confidence: 56%
“…These studies have shown that FIT is highly sensitive for detecting CRC, its accuracy for AN is adequate and it is a cost-effective test in the CRC screening setting. [20][21][22][23][24][25][26][27][28][29][30] However, no studies have compared the diagnostic accuracy between these populations of a quantitative FIT so far. Only one recently published study has compared the diagnostic yield of a qualitative FIT in these two populations, and the authors did not find differences in FIT yield either.…”
Section: Discussionmentioning
confidence: 99%
“…15,23,30 In recent years, several published studies have analyzed FIT diagnostic accuracy in familial risk CRC screening, although none of them were specifically designed to assess it. [16][17][18][19]23,[30][31][32][33][34][35] Our study confirms previous data showing a high sensitivity and specificity for CRC at a 100 ng/ml positive threshold, reaching 100 and 90%, respectively. However, diagnostic accuracy for AN was lower in our study.…”
Section: Discussionmentioning
confidence: 99%